Relationship Between Elderly Perception of Posyandu Service Quality and Elderly Satisfaction Level in Air Besar Public Health Center Work Area In 2025 - Mufidah Mufidah; Elpira Asmin; Genevieva E. Tanihatu; Ritha Tahitu; Grace Latuheru; Lidya B. E. Saptenno (Universitas Ibn Khaldun Bogor, 2026)
Posyandu for the elderly is a community-based primary health care service aimed at improving the quality of life of the elderly through routine health monitoring, education, and basic check-ups. In the Air Besar Community Health Center working area, this program has been running, but the participation rate is still low. Of the 1,275 elderly registered, only 120 (9.4%) were recorded as utilizing this service. This low number of visits indicates the need to evaluate the elderly's perceptions of the quality of Posyandu services and their relationship with their level of satisfaction. This study aims to determine the relationship between the elderly's perceptions of service quality and their level of satisfaction. This study design was quantitative analytical with a cross-sectional approach and used a consecutive sampling technique on 98 elderly respondents. The instrument was a questionnaire that had been tested for validity and reliability. Data were analyzed using the Spearman Rank correlation test. The results showed that the elderly's perception of service quality was in the good category. The empathy dimension had the highest correlation with satisfaction (r = 0.535), followed by assurance (r = 0.428), reliability (r = 0.420), responsiveness (r = 0.415), and tangible (r = 0.394). In conclusion, the quality of integrated health post (Posyandu) services is positively related to elderly satisfaction. Recommendations include increased promotion, personalized approaches to reach male elderly, training new cadres, and mobile Posyandu visits for elderly with physical or geographical limitations.